Islamic Counseling Communication Addressing Bullying and Academic Anxiety among Madrasah School Students - Lukis Alam; Failasufah; Mohamad Hilmi Bin Mat Said (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines the role of Islamic counseling in addressing bullying and academic anxiety among students at MAN 3 Sleman, with a particular focus on how counselors communicate Islamic values during counseling sessions. Unlike previous studies that primarily assess the effectiveness of Islamic counseling, this research explores the interactive communication processes that occur within counseling interactions. Using a qualitative approach, data were collected through interviews, classroom observations, and document analysis involving guidance counselors and students. The findings identify key communication strategies, including empathetic dialogue, the integration of spiritual concepts, and moral persuasion. These strategies function not only to transmit religious values but also to support students’ emotional regulation, ethical understanding, and coping abilities. This study contributes to the literature by conceptualizing Islamic counseling as an interactive communicative process and proposing a contextual counseling model that addresses students’ emotional and spiritual needs within madrasah settings.